Biology of rice moth Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) in laboratory condition - Bhat, Binu; Bajracharya, Ajay Shree Ratna; Upadhyay, Gayatri; Acharya, Sushrita (Journal of Nepal Agricultural Research Council, 2025)
Corcyra cephalonica (Stainton) is a storage insect of cereals used as factitious host for laboratory mass production of different parasitoids and predators. Various biocontrol agents are reared in C. cephalonica eggs; thus, biology of the insect needs to be well understood for successful mass production of bio-control agent. Considering the fact, biology of C. cephalonica was studied at 27±2°C temperature and 70 ±5% relative humidity in laboratory of National Entomology Research Center during 2024. Life cycle of rice moth consists of four stages: egg, larva, pupa and adult. Average egg duration of the insect was found 3.91 days. The larva passed through seven instars and average duration of each instar was found 4.98, 3.23, 3.52, 3.60, 4.93, 6.47, 10.20 days, respectively. Average pupal period was recorded 9.44 days. The mean adult longevity of male and female moths was recorded as 9.54 and 6.67 days, respectively. The pre-oviposition, oviposition and post-oviposition days of female moth was 1.09, 5.13 and 1.90 days, respectively with average fecundity of 468.3 eggs per female. The morphometric measurement showed that average length and breadth of egg was 0.57 mm and 0.37 mm. The mean length and breadth of larval instars were 1.35, 2.15, 3.50, 4.52, 6.38, 8.28, 15.50 mm and 0.21, 0.37, 0.46, 0.70, 0.92, 1.29 and 2.64 mm, respectively. Female pupae and adult moths were found larger than males. Average length of female and male pupae was 10.61 and 8.84 mm, respectively. Length and breadth of female moth was measured 10.61 and 2.23 mm whereas male moths were measured 8.84 and 1.97 mm, respectively. The width of head capsules of larval instars measured 0.22, 0.31, 0.43, 0.62, 0.81 and 0.04 mm, respectively.